Cambarus ocoeensis, a new species of crayfish (Decapoda: Cambaridae) from the Ocoee River Basin of Tennessee, USA - Thoma, Roger F.; Williams, Bronwyn W. (Zootaxa, 2025)
Cambarus ocoeensis sp. nov. is described from the Ocoee River Gorge area of Tennessee. The species is morphologically most similar to Cambarus hiwasseensis Hobbs, 1981, but differs from C. hiwasseensis in the following ways: first pereopod chelae in general less sculpted, usually with one row of palmer tubercles, if second row present very weakly developed and consisting of six or fewer tubercles, lateral margin not costate, lateral impression weak at most but usually absent; areola length 2.5–4.1 times greater than width, having 5–8 punctations in narrowest part; size at maturity smaller with MI ranging from 21.8 to 30.9 mm total carapace length (24.6–40.0 mm in C. hiwasseensis); and antennal scale broadest at midpoint. It can be distinguished from other morphologically similar species—those with acuminate rostra—from the Hiwassee River basin of northern Georgia, southeast Tennessee, and western North Carolina area in lacking lateral rostral spines/tubercles and cervical spines. Cambarus ocoeensis sp. nov. is genetically most closely related to an undescribed member of the Cambarus bartonii (Fabricius, 1798) species complex.